AN APPLIED RESEARCH ON INTEGRATING READING AND SPEAKING ACTIVITIES TO FOSTER CRITICAL THINKING IN EFL STUDENTS - Yokie Prasetya Dharma; Ilinawati Ilinawati; Ferdinanda Itu Meo (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
This study explored the impact of an integrated reading–speaking instructional model, From Text to Talk, on the critical-thinking, reading comprehension, and oral communication skills of 32 third-semester EFL students at STKIP Persada Khatulistiwa Sintang. Using a one-group pretest–posttest design, the students’ mean score rose from 45.88 (SD = 19.65) to 63.97 (SD = 11.70); a paired-samples t-test revealed a significant difference (t(31) = 10.65, p < .001) with a large effect size (Cohen’s d = 1.88). Qualitative interviews with six students uncovered key challenges — including anxiety, vocabulary and pronunciation issues, and classroom monotony — yet also highlighted gains in critical engagement, text interpretation, and spoken interaction. By triangulating quantitative and qualitative data, the study confirms that the integration of reading and speaking fosters deeper cognitive processing, authentic communication practice, and more consistent performance across learners. It further suggests the importance of scaffolded speaking tasks, emotionally safe environments, varied interactive activities, and recognition of reading as a springboard to oral reasoning in EFL instruction.